2009
DOI: 10.1007/s11060-009-0064-5
|View full text |Cite
|
Sign up to set email alerts
|

The expression level of sphingosine-1-phosphate receptor type 1 is related to MIB-1 labeling index and predicts survival of glioblastoma patients

Abstract: Although there are many reports on the clinical use of the MIB-1 labeling index (LI), which is a measure of proliferative activity in astrocytomas; its significance varies between studies. There are no known molecules that are directly linked to the MIB-1 LI in astrocytomas. We evaluated the clinical value of the MIB-1 LI in our human glioblastoma cases and determined the molecules that possibly influenced the MIB-1 LI. An immunohistochemical study of the MIB-1 protein was performed and MIB-1 LIs of 38 gliobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 35 publications
7
33
0
Order By: Relevance
“…Previous studies have shown that S1P‐SIPRs signaling can enhance cell proliferation and migration. The high S1PR1 expression in glioblastoma patients was positively associated with favorable survival 42. However, S1PR2 signaling negatively regulates tumor angiogenesis and tumor growth in vivo 43.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that S1P‐SIPRs signaling can enhance cell proliferation and migration. The high S1PR1 expression in glioblastoma patients was positively associated with favorable survival 42. However, S1PR2 signaling negatively regulates tumor angiogenesis and tumor growth in vivo 43.…”
Section: Discussionmentioning
confidence: 99%
“…Of the candidate studies, 13 articles failed to completely describe the available survival data. Finally, 51 published studies in total were included in the analysis after eliminating articles unsatisfying the selection criteria and duplicates (Jaros et al, 1992;Torp et al, 1992;Montine et al, 1994;Ellison et al, 1995;Heegaard et al, 1995;Kros et al, 1996;Coons et al, 1997;Pollack et al, 1997;Dehghani et al, 1998;McKeever et al, 1998;Ritter et al, 1998;Figarella-Branger et al, 2000;Rodriguez-Pereira et al, 2000;Ho et al, 2001;ReaveyCantwell et al, 2001;Zhong et al, 2001;Bredel et al, 2002;Pollack et al, 2002;Bowers, 2003;Chiang et al, 2003;Neder et al, 2003;Wessels et al, 2003;Zamecnik et al, 2003;Preusser et al, 2005;Uematsu et al, 2005;Kleinschmidt-DeMasters et al, 2006;Donato et al, 2007;Kanamori et al, 2008;Kuo et al, 2009;Laks et al, 2009;Li et al, 2009;Armstrong et al, 2010;Nabika et al, 2010;Watanabe et al, 2010;Yoshida et al, 2010;Habberstad et al, 2011;Margraf et al, 2011;Qiang et al, 2011;Shen et al, 2011;Zawrocki et al, 2011;…”
Section: Studies Selection and Characteristicsmentioning
confidence: 99%
“…In-turn, S1P 1 signalling is necessary for persistent Stat3 activation, forming a positive feedback loop, both within the tumour cells and in the stromal support cells, that fuels the development and growth of melanoma or bladder tumour xenografts, as well as inflammation-induced colon cancer [71,124]. In an interesting contrast to these findings, expression of the S1P 1 receptor suppresses glioblastoma growth and malignancy, despite the established association of SPHK1 with increased glioblastoma malignancy [92,125,126]. …”
Section: Studies On Individual Enzymes and Sphingolipid Metabolitementioning
confidence: 99%